Bentonitas modificadas com óxidos metálicos de Zn, Ce ou Cu aplicadas para a produção de biodiesel - Farias, Ana Flávia Félix (2016)
Clay minerals have attracted significant attention for use in heterogeneous catalysis, showing high versatility and low cost, besides their structural properties allow modifications by activation in order to obtain active catalysts. Otherwise, metallic oxides, like ZnO, CuO and CeO2, are promising materials in the catalysis for the biodiesel synthesis, whether pure or in mixtures and supported materials. Due to the search for catalysts that facilitate the separation and purification processes of the final productof transesterification, this research aimed to study the viability of ZnO, CuO and CeO2 synthesis and their simultaneous deposition on bentonite (natural and on its acid form). Moreover, the formation of ZnO/Bentonite hybrids was also evaluated. The microwave assisted hydrothermal/solvothermal method was employed to obtain the catalysts. A factorial design 23 was employed to evaluate the different experimental conditions for the synthesis of hybrids. The catalysts were characterized by X-ray diffraction, N2 adsorption, field emission scanning electronic microscopy, transmission electronic microscopy, thermogravimetry, X-ray fluorescence and infrared spectroscopy. Biodiesel synthesis was carried out using the Parr reactor, employing ethyl alcohol and soy bean. For the tests using the hybrids, the influence of the catalyst on biodiesel production was evaluated using a factorial design 22. The products of catalytic tests were characterized by kinematic viscosity, 13C and 1H nuclear magnetic resonance spectroscopy (NMR) and gas chromatography (GC).The results indicated that the natural bentonite is a good support for the formation of the catalysts obtained by microwave assisted hydrothermal/solvothermal method, showing effective whether for the formation of impregnated bentoniteon metallic oxides or hybrids synthesis. Among the metallic oxides, ZnO showed the highest activity. The factorial design allowed to identify that the pH factor for the catalysts and the temperature one for the biodiesel were the parameters that had more influence in the synthesis. The use of ZnO as active phase for the formation of the impregnated bentonite catalysts and hybrids increases the catalytic activity for transesterification reaction, achieving more than 73% yield after 4 hours of reaction and adding value to the bentonite.